2005
DOI: 10.1007/s11104-005-1361-1
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous nitrogen losses and ammonia volatilization measurement following land application of cattle slurry in the mid-Atlantic region of the USA

Abstract: To provide locally-determined field data for extension and environmental management purposes, gaseous N losses were measured following cattle slurry application to an arable silty-loam soil in the mid-Atlantic region of the USA. The field had been cropped to no-till maize. NH 3 volatilization was measured with the micro-meteorological, integrated horizontal flux (IHF) method, and denitrification with a core incubation method using acetylene inhibition. An early-winter surface application (5 December 1996; 88 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Recently converted no-till soils typically have higher bulk density and slower infiltration rate than tilled soils (Lindstrom and Onstad 1984). Accordingly, ammonia losses reached 70% of applied TAN after cattle slurry (Thompson and Meisinger 2004) and 20% after pig slurry (Rochette et al 2001) were applied to no-till soils.…”
Section: Introductionmentioning
confidence: 98%
“…Recently converted no-till soils typically have higher bulk density and slower infiltration rate than tilled soils (Lindstrom and Onstad 1984). Accordingly, ammonia losses reached 70% of applied TAN after cattle slurry (Thompson and Meisinger 2004) and 20% after pig slurry (Rochette et al 2001) were applied to no-till soils.…”
Section: Introductionmentioning
confidence: 98%
“…522 C. Spirig et al: The annual ammonia budget of fertilised cut grassland Ammonia exchange over agricultural fields has been investigated in numerous studies (Sutton et al, 1993a, b;Herrmann et al, 2001;Spindler et al, 2001; Thompson and Meisinger, 2004;Walker et al, 2006) using micrometeorological techniques especially the aerodynamic gradient method (AGM) and more recently relaxed eddy accumulation .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike background exchange, which exhibits rather regular diurnal and seasonal patterns controlled by meteorology and grassland growth and phenology, peak emissions from fertiliser application are characterized by strong asymmetrical dynamics over a few days with successive pulses of decreasing strength. The emission flux and NH 3 surface concentration thus decrease rapidly, broadly following an exponential decay curve (Spirig et al, 2010;Génermont et al, 1998;Thompson and Meisinger, 2004) back to values close to those observed prior to fertilisation.…”
Section: Introductionmentioning
confidence: 54%